2015
DOI: 10.7740/kjcs.2015.60.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Growing Environment Influence the Anthocyanin Content in Purple- and Red-Fleshed Potatoes During Tuber Development

Abstract: This study was carried out to determine environmental factors affecting the anthocyanin content of colorfleshed potato (Solanum tuberosum L.) tubers. After planting of two color-fleshed potato cultivars of 'Hongyoung' and 'Jayoung' in different 14 locations, their soil chemical properties and meteorological data were evaluated, and anthocyanin contents of tubers were analyzed after harvest, additionally their relationship among them was analyzed through correlation analysis. In comparison with two cultivars, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Anthocyanins are responsible for the red and blue color of B. juncea leaves, and the color intensity varies depending on the cultivation conditions. A high level of anthocyanins reportedly requires blue light, cool climate, and a large daily temperature range [34][35][36]. Consistently, in the field experiment, B. juncea cultivated in the cool outdoor field environment exhibited a relatively higher level of anthocyanin production, whereas B. juncea cultivated in the glass greenhouse under higher temperatures resulted in intense light-green-to-green leaves according to hyperspectral imaging.…”
Section: Analysis Of Plant Pigments and Metabolitessupporting
confidence: 67%
“…Anthocyanins are responsible for the red and blue color of B. juncea leaves, and the color intensity varies depending on the cultivation conditions. A high level of anthocyanins reportedly requires blue light, cool climate, and a large daily temperature range [34][35][36]. Consistently, in the field experiment, B. juncea cultivated in the cool outdoor field environment exhibited a relatively higher level of anthocyanin production, whereas B. juncea cultivated in the glass greenhouse under higher temperatures resulted in intense light-green-to-green leaves according to hyperspectral imaging.…”
Section: Analysis Of Plant Pigments and Metabolitessupporting
confidence: 67%
“…[ 26 ] reported that the growing environment, including altitude and soil factors, significantly increase anthocyanin production but have no effect on carotenoids. A Korean study [ 41 ] showed that anthocyanins responded well to high-altitude areas in comparison to those cultivated in a low-lying area over a two-year period and in 14 different locations. These authors also reported a negative correlation between soil acidity and anthocyanin contents.…”
Section: The Impact Of Environmental Genotypic and Soil Types On Pigmented Potato Characteristicsmentioning
confidence: 99%
“…; Jeong et al . ), have been made to fortify these antioxidant components in colored potatoes. The colored potato cultivars, “Hongyoung” and “Jayoung,” red and purple potatoes, respectively, were recently bred by the National Institute of Crop Science (Korea) in order to make anthocyanin‐enriched potatoes that could be used not only for regular food but also as a raw material for functional food (Park et al .…”
Section: Introductionmentioning
confidence: 99%
“…The health functions of colored potatoes are thought to be due to their antioxidant capacity, and their antioxidative activities come from antioxidant phytochemicals, mainly anthocyanins and hydroxycinnamates (Lachman and Hamouz 2005;Madiwale et al 2011;Nayak et al 2011a). Various efforts, such as the optimization of storage conditions and processing methods (Madiwale et al 2011;Nayak et al 2011a;Nayak et al 2011b;Nems et al 2015) as well as increasing the anthocyanin content of the raw potatoes by breeding and cultivation (Park et al 2009a;Park et al 2009b;Jeong et al 2015), have been made to fortify these antioxidant components in colored potatoes. The colored potato cultivars, "Hongyoung" and "Jayoung," red and purple potatoes, respectively, were recently bred by the National Institute of Crop Science (Korea) in order to make anthocyanin-enriched potatoes that could be used not only for regular food but also as a raw material for functional food (Park et al 2009a;Park et al 2009b).…”
Section: Introductionmentioning
confidence: 99%